Designing Targeted Business Trainings for Impact : Insights from a Women Entrepreneurs' Program in Tanzania - Bardasi, Elena; Gassier, Marine; Goldstein, Markus; Holla, Alaka (World Bank, Washington, DC, 2018)
Business training in low-income countries have scarcely shown impacts on revenues and profits, especially for female entrepreneurs. In this study, we test two kinds of trainings, one basic in-class training and one enhanced version supplemented with individualized coaching, to test their respective impact on women with established small businesses in Tanzania. We found that targeting the right entrepreneurs can improve the effectiveness of a tailored training and even lead to improvements in performance. We also determined that the content and delivery method of business support provided to the female entrepreneurs impact their adoption of business practices.